THE ARRANGEMENT OF MODERN RETAIL INDUSTRY IN THE PERSPECTIVE OF POSITIVE LAW IN INDONESIA - Sandra Megayanti; Candra Irawan; Emelia Kontesa (Universitas Bengkulu, 2020)
Indonesia is a state law that all aspects of life in the areas of society, nationality and state affairs including government affairs should be based on the law in accordance with the national legal system, not least in terms of the economy. Economy is the backbone of public welfare, while the law plays an important role that determines how the prosperity achieved and felt by the people. One of the industries that participate in contributing to the growth and development of the Indonesian economy is the modern retail industry. The existence of the modern retail industry as having two sides of a coin, which on the one hand its existence becomes an important part in the economy, one of them in terms of employment. However, on the other hand, the existence of the modern retail industry raises problems, one of which is the rise of this industry makes the small and medium businesses cannot compete. Nevertheless, the existence of modern retail is currently being faced with adverse situations, where there are a lot of modern retailers who had to close their shops in a number of places, in addition, the proliferation of online businesses also adds problems in the modern retail industry. This study aimed to analyze the arrangement of modern retail industry in the perspective of Indonesian positive law. In this case, researcher used a normative legal research methods with qualitative juridical analysis. In terms of setting, the existence of the modern retail industry has not been able to provide its effectiveness in achieving fairness, certainty and expediency. Currently, the setting of modern retail industry could be seen in some rules, such as Law No. 7 of 2014 About the Trade, Law No. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Competition, Law No. 25 of 2007 on Investment, President Regulation No. 112 of 2007 on Planning and Development of Traditional Markets, Shopping Centers and Modern Stores, and Government Regulation No. 44 of 1997 concerning the Partnership. However, the implementation of these regulations have not been going well because there is no consistency in the process of administration of justice, both by governments and businessesactors.